Pelatihan Pemanfaatan Minyak Jelantah Menjadi Lilin Aroma Terapi sebagai Pencegahan Pencemaran Lingkungan dan Peningkatan Keterampilan Masyarakat di Desa Gebanganom Kabupaten Kendal - Azni Aliyafi; Azka Faqih Fasihullisan; Moh Danish Andriansyah; Dian Ika Aryani (Lembaga Pengembangan Kinerja Dosen, 2024)
Abstract and Keywords must be written in English, in italic style, and contain a brief description of the research background, objectives, methods, findings, and implications. The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or for This community service was carried out with the aim of providing skills in making aroma therapy candles from used cooking oil and increasing awareness of the importance of processing used cooking oil to create environmentally friendly products. In this training, in the future it is hoped that it can increase awareness of the importance of wise processing of used cooking oil waste to mothers in Gebanganom Village. The Aroma Therapy Candle Making Training was held on Saturday, August 3, 2023. As a result of the training, the women in Gebanganom Village were very enthusiastic and excited. With the enthusiasm and activeness of the women, this training was successful and beneficial for the village community.